1908
DOI: 10.1111/j.1469-8137.1908.tb06068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dispersal of Fruits and Seeds by Ants.

Abstract: [TBXT-FIO. 2]. BOTH to those who are interested in the biology of plants and to those engaged in the study of plant ecology, Sernander's " Entwurf einer Monographie der Europaischen Myrmekochoren'," will be a welcome source of information. Already in an earlier Swedish publication^ (with German summary) Sernander had distinguished three ways which animals might aid in the dispersal of seeds and fruits. If feeding on succulent fruits they pass the seeds through the alimentary canal, he applies the name of endoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…odorata). Our results confirm that not all elaiosomes were eaten by ants during the nest stage Servigne and Detrain 2008;Weiss 1908). The consequences of such variability in the dynamics of elaiosome detachment and seed rejection may be important in terms of fitness for each partner.…”
Section: Seed Rejectionsupporting
confidence: 85%
“…odorata). Our results confirm that not all elaiosomes were eaten by ants during the nest stage Servigne and Detrain 2008;Weiss 1908). The consequences of such variability in the dynamics of elaiosome detachment and seed rejection may be important in terms of fitness for each partner.…”
Section: Seed Rejectionsupporting
confidence: 85%
“…Kollmann and Bassin 2001). Our findings are consistent with earlier reports (Weiss 1908;Pemberton and Irving 1990; Alba-Lynn and Henk 2010) which suggested that the structures at the distal end of the seeds function as ant-attracting elaiosomes. It would therefore be more correct to refer to these thistle species as not only wind-dispersed and human-dispersed, but, within populations, also as ant-dispersed.…”
Section: Discussionsupporting
confidence: 95%
“…Previous studies of these species have focused on floral herbivory that causes seed losses in C. nutans (Sheppard et al 1994;Marchetto et al 2014) and on the pre-dispersal seed predation of C. nutans by goldfinches (Kelly and McCallum 1990). However, the seeds of these thistles not only have plumes for wind dispersal, but also elaiosomes (Weiss 1908;Pemberton and Irving 1990) and thus attract ants which might serve as secondary dispersal vectors (Alba-Lynn and Henk 2010). The goal of this study is therefore to shed light on this less wellknown stage of the thistle life cycle: post-dispersal seed removal.…”
Section: Introductionmentioning
confidence: 99%
“…Northern hemisphere myrmecochores belong to genera such as Uvularia (Robertson 1897; ; Ulex (Weiss 1908(Weiss , 1909; Roseoea and Cautleya (Nordhagen 1932a, b); Trillium (Gates 1940(Gates , 1941; Sanguinaria, Hepatiea and Viola (Gates 1942;Pudlo et al 1980);andCarex, Luzula andClaytonia (Randel 1976, 1978a). Northern hemisphere myrmecochores belong to genera such as Uvularia (Robertson 1897; ; Ulex (Weiss 1908(Weiss , 1909; Roseoea and Cautleya (Nordhagen 1932a, b); Trillium (Gates 1940(Gates , 1941; Sanguinaria, Hepatiea and Viola (Gates 1942;Pudlo et al 1980);andCarex, Luzula andClaytonia (Randel 1976, 1978a).…”
Section: Seed Dispersalmentioning
confidence: 99%